Product Quality for Smart Cities Applications: A Mapping Study - Machado, Leonardo Ribeiro; Silva, Francisco José; Barradas, Alex Oliveira; Viana, Davi; Teles, Ariel Soares; Coutinho, Luciano Reis (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2020.13773, 2020)
In recent years, the domain of applications and information systems for Smart Cities (SC) has emerged and motivated researchers and practitioners to develop relevant solutions. The development of applications for SC involves many specificities, such as: (i) processing and analysis of large volumes of data; (ii) context-awareness; (iii) perception and actuation on physical elements of the city; and (iv) maintaining citizens’ privacy and security. It is important to ensure that these specificities have an adequate level of quality that enables the daily use of these applications in these cities. However, there is still no consolidated set of properties and / or characteristics that should be considered when evaluating the quality of this specific type of application. The goal of this work is to identify the characteristics and sub-characteristics of product quality that are being considered in the evaluation of applications and information systems in the context of SC. To do this, a Mapping Study was conducted, aiming to present an overview of the current state of the art in product quality for this context. Additionally, an analysis was carried out between the product quality characteristics of the ISO / IEC 25010: 2011 model with the characteristics identified in this mapping. As a result, eight related works, which deal with characteristics, such as Reliability, Compatibility, Maintenance, and Safety have been identified. Finally, there is a need for more detailed specifications of characteristics that enable the quality assurance of SC applications.